Interaction between variants in CLU and MS4A4E modulates Alzheimer’s disease risk - Ebbert, Mark T.W. (Alzheimers Dement, 2015)
INTRODUCTION: Ebbert et al. reported gene-gene interactions between rs11136000-rs670139 (CLU-MS4A4E) and rs3865444-rs670139 (CD33-MS4A4E). We evaluate these interactions in the largest dataset for an epistasis study. METHODS: We tested interactions using 3837 cases and 4145 controls from ADGC using meta- and permutation analyses. We repeated meta-analyses stratified by APOEε4 status, estimated combined OR and population attributable fraction (cPAF), and explored causal variants. RESULTS: Results support the CLU-MS4A4E interaction and a dominant effect. An association between CLU-MS4A4E and APOEε4 negative status exists. The estimated synergy factor, OR, and cPAF for rs11136000-rs670139 are 2.23, 2.45 and 8.0, respectively. We identified potential causal variants. DISCUSSION: We replicated the CLU-MS4A4E interaction in a large case-control series, with APOEε4 and possible dominant effect. The CLU-MS4A4E OR is higher than any Alzheimer’s disease locus except APOEε4, APP, and TREM2. We estimated an 8% decrease in Alzheimer’s disease incidence without CLU-MS4A4E risk alleles and identified potential causal variants.